PEMANFAATAN LINGKUNGAN SEKOLAH OLEH GURU SEBAGAI PEMBELAJARAN NYATA MATERI EKOSISTEM MATA PELAJARAN IPAS KELAS V SD - Lestari, Nanda; Chan, Faizal; Pamela, Issaura Sherly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning natural and social sciences, specifically the ecosystem material in elementary schools, requires the direct involvement of students so that the concepts can be understood concretely and contextually. However, the use of the school environment as a source of real learning has not been fully optimized by teachers. This study aims to describe the utilization of the school environment by teachers as real learning in the ecosystem material of fifth-grade natural and social science subjects, as well as to identify the challenges faced in its implementation.Keywords: school environment utilization, real learning, ecosystem, Natural and Social Sciences elementary school. This study used a qualitative approach with a case study type conducted at SD Negeri 014/I Sungai Baung. The research subjects included the principal, fifth-grade teachers, and fifth-grade students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that teachers have utilized the school environment as real learning by making use of biotic and abiotic components such as plants, small animals, soil, water, and sunlight. This utilization helps students understand the concept of ecosystems more concretely and increases active involvement in learning. However, the use of the school environment has not been carried out optimally and systematically. The challenges faced include limited class time, a lack of structured planning for outdoor learning, limited supporting facilities, and teachers' experience in managing environment-based learning. Therefore, more thorough planning and school support are needed so that the utilization of the school environment as real learning can be implemented sustainably.